Realities, perceptions, and strategies for implementation of an ethical population management program for dogs and cats on university campuses - Bicalho, Gustavo Canesso; Oliveira, Lucas Belchior Souza de; de Oliveira, Camila Stefanie Fonseca; Costa Val Bicalho, Adriane Pimenta Da; Bastos, Camila Valgas; Torres, Camila Machado; Malm, Christina; de Souza, Fernanda Louro; Lima, Graciela Kunrath; Maia, Lorena Diniz Macedo Silva; Villalta, Luiz Carlos; de Carvalho, Marcelo Pires Nogueira; et al. (Frontiers in Veterinary Science, 2024)
Stray dogs and cats pose significant challenges for public health and animal welfare due to their potential involvement in zoonotic disease transmission, accidents, and aggressions. Large urban centers exacerbated challenges due to the presence of these animals in public areas with high human density. Ethical Population Management Programs (EPMP), rooted in the One Health approach, are crucial for addressing this issue comprehensively. This study aimed to demonstrate the approach on cats and dogs EPMP and evaluate the perceptions of academic community regarding EPMP implementation on a campus situated in urban territory. The study was conducted at the Pampulha campus of UFMG in Belo Horizonte, Brazil. In response to issues of animal abandonment and conflicts, the Permanent Commission for Animal Policies (CPPA-UFMG) was established in 2019 to manage the campus's dog, cat, and wildlife populations. The commission implemented the Trap-Neuter-Return (TNR) method, along with health assessments and vaccinations for animals. Interviews were conducted with campus staff to gauge their perception of animal management strategies. Retrospective and prospective analyses of the commission's actions were carried out to assess implementation processes and challenges. The animal population survey conducted on campus between July 2018 and September 2021 revealed a total of 266 animals recorded. Among these animals, 195 were cats (73.3%) and 71 were dogs (26.7%), with the majority being adults. Subsequent surveys in 2019 and 2021 showed a slight increase in the animal population, with measures such as sterilization contributing to population control. Perception analysis among campus users indicated strategies such as TNR were widely endorsed for population control. The employees perception questionnaire was applied to 115 individuals, representing 42 units/departments and five gates. Associations were found between these beliefs and support for institutional actions. The majority favored sterilization (92.17%) and agreed that TNR is an appropriate approach to population control. Overall, the study reflects a community concerned about animal welfare and supportive of measures to address population management and cruelty prevention. The continuous efforts of the university's CPPA have led to stability in the resident animal population, indicating success in achieving population control objectives.